Legal Analysis Of The Implementation Of The Presidential Threshold In General Elections In Indonesia - Kausar Jumahir Lesen (Cita konsultindo, 2025)
Presidential Threshold concept reduces the rights of everyone to get equal opportunities in government. Constitutional Court Decision Constitutional Court Decision Number 14/PUUXI/2013 which decided that the Presidential and Vice Presidential Elections were held simultaneously with the Elections of the People's Representative Council or known as simultaneous elections. The regulation of the presidential nomination threshold (Presidential Threshold) is essentially an open legal policy. The source of attribution authority in the constitution, especially in Article 6A paragraph (2) and Article 22E paragraph (6) of the 1945 Constitution of the Republic of Indonesia as a higher legal norm, does not regulate or provide restrictions for anyone who wants to nominate themselves as a candidate for President and Vice President. The existence of a threshold for political parties to have the right to nominate presidential and vice-presidential candidate pairs has legal implications, including violating the 1945 Constitution concerning the Presidential System, contradicting Article 6A paragraph (2) of the 1945 Constitution, the inconsistency of the Constitutional Court in Decision Number 14/PUU-XI/2013 and violating the rights of citizens in the 1945 Constitution.